Babari sebagai Modal Sosial Penguatan Ketahanan Ekonomi Petani dalam Perspektif Syariah - Nurul Hidayah; Nurlaila Nurlaila; Dewi Permatasari (Fakultas Syariah IAIN Kerinci, 2026)
Babari is a local wisdom of non-market collective labor among indigenous communities in North Maluku, relying entirely on collective social memory and customary norms. This conceptual study refers to the sociological characteristics of coconut farmers in Indonesia who utilize social capital strengthening to cope with limited access to agricultural production resources. This study aims to analyze the economic function of Babari as farmers' social capital, evaluate its mechanism through the principles of ta‘awun and maqāṣid al-syarī‘ah, and formulate a revitalization model for inclusive farmers' economic empowerment. The method employed is qualitative literature-based research with conceptual and normative approaches. The research data consists of literature retrieved from the Google Scholar database, which was analyzed through concept reduction, functional mapping, normative testing, and policy synthesis. The findings indicate that Babari functions as an informal economic institution that effectively reduces cash production costs for coconut farming, shares risks, and strengthens household economic resilience. Normatively, Babari aligns with the concept of ta‘awun ṣaḥīḥ (valid mutual assistance) and supports maqāṣid al-syarī‘ah in terms of wealth protection and social cohesion, despite risks of social exclusion and gender burdens that require correction. Revitalizing Babari requires inclusive institutional integration with farmers' groups, Islamic cooperatives, and zakat institutions. Future research needs to be directed toward quantitative empirical field testing to measure the direct impact of Babari on the actual productivity of coconut farming households.